2020
DOI: 10.3389/fimmu.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Dengue ED3 Long-Term Immune Response With T-Cell Memory Generated Using Solubility Controlling Peptide Tags

Abstract: Recombinant proteins are an attractive choice as a safe alternative to traditional live attenuated vaccines. However, most small-size proteins are poorly immunogenic, and adjuvants, whose mode of action remain to be fully clarified, are needed for increasing their immunogenicity. Here, we report the effects of short solubility controlling peptide tags (SCP-tags) on the immunogenicity of DENV3 envelope protein domain 3 (3ED3; 103 residues, 11.46 kDa) in ICR and Swiss albino model mice. The attachment of a 4-Ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 47 publications
(61 reference statements)
4
32
1
Order By: Relevance
“…In previous reports, we showed that short solubility controlling peptide tags (SCP‐tags) [11–13] attached at the C terminus of a host protein could be used to induce the formation of subvisible amorphous aggregates and thereby increase the immunogenicity of non‐immunogenic proteins [14,15]. In particular, a hydrophobic isoleucine tag attached to the C terminus of two model proteins, BPTI‐19A (58 residues; MW: 5.98 kDa) and DEN3ED3 (103 residues; MW 11.46 kDa), increased their immunogenicity by oligomerizing the proteins into small nanometer‐scale aggregates, and the immune response was long‐lasting with a T‐cell‐dependent activation of the B cells [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, we showed that short solubility controlling peptide tags (SCP‐tags) [11–13] attached at the C terminus of a host protein could be used to induce the formation of subvisible amorphous aggregates and thereby increase the immunogenicity of non‐immunogenic proteins [14,15]. In particular, a hydrophobic isoleucine tag attached to the C terminus of two model proteins, BPTI‐19A (58 residues; MW: 5.98 kDa) and DEN3ED3 (103 residues; MW 11.46 kDa), increased their immunogenicity by oligomerizing the proteins into small nanometer‐scale aggregates, and the immune response was long‐lasting with a T‐cell‐dependent activation of the B cells [16,17].…”
mentioning
confidence: 99%
“…Thus, in addition to the previously reported C5I tag, which increased immunogenicity through protein oligomerization, C5P and C5R tags are expected to provide a tool for increasing a protein's immunogenicity without any oligomerization. [14].…”
mentioning
confidence: 99%
“…ELISA was performed as previously reported [14]. In short, anti-BPTI IgG levels were evaluated using untagged BPTI-19A (2.5 µg/mL in PBS) as coating antigen on the 96-well microtiter plates (TPP microtiter plates, Japan).…”
Section: Elisamentioning
confidence: 99%
“…In previous reports, we showed that short Solubility Controlling Peptide tags (SCP-tags) [11,12,13] attached at the C-terminus of a host protein could be used to induce the formation of sub-visible amorphous aggregates and thereby increase the immunogenicity of nonimmunogenic proteins [14,15]. In particular, a hydrophobic isoleucine tag attached to the Cterminus of two model proteins, BPTI-19A (58 residues; MW: 5.98 kDa) and DEN3ED3 (103 residues; MW 11.46 kDa) increased their immunogenicity by oligomerizing the proteins into small nanometer-scale aggregates, and the immune response was long-lasting with a T-celldependent activation of the B-cells [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation